2018
DOI: 10.1007/s12035-018-1243-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin 1, 2, and 3 Regulation at the Synapse: FMRP-Dependent Translation and Activity-Induced Proteolytic Cleavage

Abstract: Neuroligins (NLGNs) are cell adhesion molecules located on the postsynaptic side of the synapse that interact with their presynaptic partners neurexins to maintain trans-synaptic connection. Fragile X syndrome (FXS) is a common neurodevelopmental disease that often co-occurs with autism and is caused by the lack of fragile X mental retardation protein (FMRP) expression. To gain an insight into the molecular interactions between the autism-related genes, we sought to determine whether FMRP controls the synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 72 publications
(146 reference statements)
2
23
0
1
Order By: Relevance
“…1076 Neuron 101, March 20, 2019 Neuron Review 2013). Of note, NLGNs promote synaptic transmission (Varoqueaux et al, 2006) and are regulated by FMRP at synapses (Chmielewska et al, 2018;Darnell et al, 2011;Pasciuto and Bagni, 2014b).…”
Section: Fmrp Differently Recognizes Neuronal Mrnasmentioning
confidence: 99%
“…1076 Neuron 101, March 20, 2019 Neuron Review 2013). Of note, NLGNs promote synaptic transmission (Varoqueaux et al, 2006) and are regulated by FMRP at synapses (Chmielewska et al, 2018;Darnell et al, 2011;Pasciuto and Bagni, 2014b).…”
Section: Fmrp Differently Recognizes Neuronal Mrnasmentioning
confidence: 99%
“…FMRP plays a key role in the dynamic regulation of the synaptic proteome. FMRP associates with Nlgn1 , Nlgn2 and Nlgn3 mRNAs; consequently, Fmr1 KO leads to elevated local translation of Nlgn mRNAs and increased targeting of Nlgn1 and Nlgn3 to postsynaptic membranes (Chmielewska et al, 2018). FMRP binds to a G-rich region of PSD-95 mRNA, and together with microRNA miR-125a, plays an important role in the reversible inhibition of PSD-95 mRNA translation in neurons (Muddashetty et al, 2011; Stefanovic et al, 2015).…”
Section: Synaptic Gene Transcription Protein Synthesis and Degradationmentioning
confidence: 99%
“…For each of the 23 mouse genes whose transcripts bind FMRP (Chmielewska et al, 2019;Darnell et al, 2011;F€ ahling et al, 2009;Muddashetty et al, 2007;Zhang, Gaetano, Williams, Bassell, & Mihailescu, 2014), we searched PubMed and OMIM (Amberger, Bocchini, Scott, & Hamosh, 2019). For 17 of the human orthologs, we found evidence that mutations cause one or more neurodevelopmental disorders (Table S1).…”
Section: Analysis Of Neurodevelopmental Disorders Caused By Mutationsmentioning
confidence: 99%
“…Among the genes whose transcripts are known to be FMRP targets (Chmielewska et al, 2019;Darnell et al, 2011;Muddashetty et al, 2007) are 17 whose mutations cause Mendelian brain-development disorders, and most of those include ASD or "autistic features" as clinical phenotypes (Table S1). Remarkably, however, for the large majority of these, laboratory-based functional analyses of the mutations demonstrated that they are loss-of-function (LOF) alleles, often with haploinsufficiency and sometimes with dominantnegative characteristics.…”
Section: Proposed Mechanism Of Excessive Repetitive Behavior In Fxsmentioning
confidence: 99%
See 1 more Smart Citation